2020
DOI: 10.1186/s13020-020-0287-0
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of aged and contemporary Chinese herbal materials by using delayed luminescence technique

Abstract: Background: Investigation of aged Chinese herbal materials will help us to understand their use and sources in ancient time and broaden the historical perspective of Chinese material medica. To reach this aim, the basic understanding of aged herbal materials, including physical and chemical characters, is of great importance. Delayed luminescence (DL) technique was developed as a rapid, direct, systemic, objective and sample loss-free tool to characterize the properties of Chinese herbal materials. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Moreover, additional research should emphasize bioactivity based quality assessments for herbs in order to promote the shift from evaluating chemical pattern to evaluating activities corresponding to the chemical constituents. In conclusion, DL provides a technique for studying the overall property of herbal materials [43], and the integrated assessment by measuring chromatographic fingerprint and DL based on bioactivity may provide a novel means to measure herbal quality control.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, additional research should emphasize bioactivity based quality assessments for herbs in order to promote the shift from evaluating chemical pattern to evaluating activities corresponding to the chemical constituents. In conclusion, DL provides a technique for studying the overall property of herbal materials [43], and the integrated assessment by measuring chromatographic fingerprint and DL based on bioactivity may provide a novel means to measure herbal quality control.…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, four category tests were selected UPE can be utilized as a fast, simple, and inexpensive method, rather than conventional techniques to identify herbal materials Gała˛zka-Czarnecka et al, 2019 Eggs Assessing the quality of eggs Two different hens, including the caged and free-range, were selected to determine their freshness and quality It was observed that UPE from free-range eggs had eight times higher intensity than eggs from caged hens. They also found that the eggs from free-range hens had more than three times higher carotenoid than eggs from caged hens Jia et al 2020 Herbal materials…”
Section: Investigating the Relation Between Seedling Growth And Upe Intensitymentioning
confidence: 98%
“…They stated that further research is needed for using the UPE method as a food quality assessment tool. Jia et al (2020) studied the aged and contemporary properties of some Chinese herbal materials, including Glycyrrhiza glabra L., Glycyrrhiza inflata Batalin, Glycyrrhiza uralensis Fisch., Curcuma aromatica Salisb., Zingiber officinale Roscoe, Acorus calamus L., and Alpinia officinarum Hance. They implemented the UPE technique by PMT devices to differentiate the aged and contemporary samples.…”
Section: Ma Nematollahi Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, DL has been used to assess the quality features of dry powders prepared from plant-derived Chinese herbal materials [10][11][12][13][14][15][16][17]. DL provides a new method for measuring plant-derived herbal materials which can be recognized as a rapid, direct and sensitive indicator of a wide range of herbs prepared in different grown environments, different age, different processing statues, as well as different therapeutic properties [11][12][13][14][15][16][17]. Thus, DL becomes a promising technique for herbal quality control, and it may become a novel tool to combine with other analytic technological platform such as high performance liquid chromatography ngerprint platform [17].…”
Section: Introductionmentioning
confidence: 99%